(untitled) (The Pretoria Student Law Review, 2021)
South Africa, like the whole of Africa and many parts of the world, was not immune to Western civilisation, and this ‘civilisation’ was accompanied by the imposition of Western ideas, laws, cultures and traditions, and many other attributes of conquest.3 African law was infiltrated and distorted beyond recognition, resulting in the origination of ‘official’ customary law, which remains stagnant and incapable of accounting for the needs, values and circumstances of an ever-changing society.4 This study looks at the battle for the Vhavenda kingship/queenship between Masindi Mphephu (hereafter ‘Masindi’) and Toni Peter Mphephu (hereafter ‘Toni’) and contends that the Supreme Court of Appeal’s decision was correct in light of the values enshrined in our constitutional democracy.5 This is done by looking at the decision pertaining to the principle of male primogeniture in Bhe and Others v Khayelitsha Magistrate and Others (hereafter ‘the Bhe case’) and succession in Shilubana and Others v Nwamitwa (hereafter ‘the Shilubana case’).6 Throughout this study, the adoption of ‘living’ customary law by judicial systems and the legislature is proposed as a catalyst towards the transformation of customary law.7 Finally, this study contends that the pronouncement of Masindi as queen would be a step towards the transformation of customary law.8